A manual for agribusiness value chain analysis in developing countries - Dent, Benjamin (CABI, 2021)
The manual shows how value chain analysis (VCA) principles can be applied in developing countries, where time and funding is often restricted. It explains how to undertake affordable VCA that generate valid data and produce recommendations that will have impact.